2020
DOI: 10.1002/hon.2718
|View full text |Cite
|
Sign up to set email alerts
|

High throughput sequencing reveals high specificity of TNFAIP3 mutations in ocular adnexal marginal zone B‐cell lymphomas

Abstract: The majority of ocular adnexal (OA) lymphomas (OAL) are extranodal marginal zone lymphomas (MZL). First high throughput sequencing (HTS) studies on OA-MZL showed inconsistent results and the distribution of mutations in reactive lymphoid lesions of this anatomic region has not yet been sufficiently addressed. We characterized OAL and lymphoid lesions of the OA by targeted HTS. The study included 34 OA-MZL, 11 chronic conjunctivitis, five mature small cell B-cell lymphomas spreading to the OA, five diseases wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 30 publications
2
30
0
Order By: Relevance
“…Due to the differing cohort numbers, mutational rates are more difficult to describe in EMZL. Ten EMZL [18,19,[33][34][35][36][37][38][39][40] studies extensively looked for TNFAIP3 and TBL1XR1 mutations and detected 140/500 and 66/515 mutant cases, respectively. A total of 29 cases with NOTCH1 mutations was found in 324 samples, while 14 cases with KMT2C mutations were identified in 135 studied instances.…”
Section: Mutational Profile Of Emzlmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the differing cohort numbers, mutational rates are more difficult to describe in EMZL. Ten EMZL [18,19,[33][34][35][36][37][38][39][40] studies extensively looked for TNFAIP3 and TBL1XR1 mutations and detected 140/500 and 66/515 mutant cases, respectively. A total of 29 cases with NOTCH1 mutations was found in 324 samples, while 14 cases with KMT2C mutations were identified in 135 studied instances.…”
Section: Mutational Profile Of Emzlmentioning
confidence: 99%
“…Two thyroid MZL (TMZL) studies [18,19] showed a high prevalence of TET2 mutations (61%, 11/18), which statistically significantly exceeded that in salivary gland In the two studies with available information on sublocalization of the OMZL (conjunctival versus periorbital) [37,38], total numbers of mutations in conjunctival OMZL were higher than in periorbital OMZL (median 2 versus 1; mean 2.38 versus 1.56, range 0-9 versus 0-5; p = 0.028). TBL1XR1 mutations were enriched in conjunctival OMZL (8/27 versus 1/17, p = 4.63E−02 [37]; 7/22 versus 0/12, p = 0.095 [38]).…”
Section: Mutational Profile Of Emzlmentioning
confidence: 99%
“…NFKBIE encodes NFKB inhibitor epsilon (NFKBIE), a negative regulator of the NF-κB pathway [ 18 ]. The NFKBIE Y254fs mutation has been reported in aggressive chronic lymphocytic leukemia (CLL), Hodgkin lymphoma (HL), DLBCL, primary mediastinal B-cell lymphoma (PMBCL) and a few cases of low-grade B-cell NHL, including follicular lymphoma (FL), EMZL [ 19 ], and SMZL [ 11 , 20 ]. However, this mutation has never been reported in patients with NMZLs.…”
Section: Discussionmentioning
confidence: 99%
“…The TNFAIP3 gene encoding A20 is highly specific to ocular adnexal lymphomas (OAL) [78]. In DLBCL, the frequency of A20 deletion is similar in germinal center B-celllike (GCB) and non-GCB DLBCL.…”
Section: Tnfaip3/a20 Genementioning
confidence: 99%